الترجمة بين الاستقلالية والتبعية: اعتباطية مفهوم الترجمة كعلمٍ مستقلٍّ - إبراهيم, ياسر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
للترجمة أهمية حيوية في التواصل الحضاري بين الأمم، حيث أغنت البشرية جمعاء بمكانتها المتميّزة بين العلوم والآداب؛ بعد أن سبقت رحلَتها إلى شاطئ الاستقلالية مرحلةٌ ليست بقصيرة جعلت منها مجالاً متأرجحاً أميل إلى التبعية والفرعية. واليوم، تشهد الترجمة تطوّراً ملحوظاً تعبّر من خلاله عن دورها الريادي في تعميق أواصر التواصل والأخذ والعطاء بين شعوب المعمورة. فأيام الازدهار العباسي للترجمة التي لخّصها المأمون بتشجيعه للمترجمين عندما كان يمنح المترجم وزن الكتاب المترجم ذهباً ليست أقلّ شأناً ممّا تتمتع به الترجمة في أيامنا هذه من أن ترجمة كتاب حديث العهد يعدّ أثراً بعيد المدى كالذي يؤلّف كتاباً تخصصياً. لقد ذهب بعض المنظرين في مجال الترجمة إلى اعتبار مفهوم التخاطب برمّته-مكتوباً أو شفهياً- شكلاً من أشكال الترجمة. ووُضعت مبادئُ عامةٌ للترجمة في مؤلفات خاصّة بعلم الترجمة (A.F. Tytler) ثمّ ظهرت تخصصات لهذه المبادئ عبّرت عن عمق التجربة الترجمية للمؤلفات العديدة في مختلف ميادين العلوم والمعرفة كمبادئ ترجمة الأدب من شعرٍ ونثرٍ ومسرح، ومبادئ ترجمة النصّ العلمي، وأنواع شتّى لتقنيات الترجمة وأساليبها. كذلك فرض ظهورها كعلم مستقلّ معايير هامّة لتدريسها ولا سيّما عملية اختيار النصّ وآلية ترجمته وتحقيق التوازن بين الأمانة العلمية والهدف الأساسي للنصّ المطروح. ويأتي هذا البحث ليجيب على تساؤل جوهري حول ماهية الترجمة وأهمية استقلالها وتمتّعها بخصائصها المنفردة علماً وفناً ومهارةً لا تقلّ شأناً عن باقي العلوم. Translation plays a vital role in civilized communication among nations, where its significance in sciences and literatures enriches humanity, at large. Its trip towards independence was preceded by a long period of dependency that put it in a shaky position. Today, translation witnesses a recognized stage of development that elaborates its pioneering role in deepening the ways, for different nations in communicating effectively. The Abbasseid Period, when translation flourished, was widely known where the Caliphate al-Mamoun extremely supported translators and specified an award like a weight of gold for a translated book. This method of assessing and encouraging translation is not so different from that of our days during which a newly translated book is compared to an authorized one. Some translation theoreticians believe that communication-oral or written-is one form of translation. Besides, principles of translation have been proposed in special authorized books (see A.F. Tytler), followed by more specialized principles of translation that express the depth of translative experience in every field of knowledge, e.g. literature (poetry, drama, and prose), scientific text, and other relevant strategies and methods. However, its appearance as an independent science has expounded important criteria for teaching it, especially in what affects the choice of the text, the methodology of translating it, and 'scientific' faithfulness, besides the ultimate goal after its rendition. This piece of research aims at answering a vital question about confirming the independence of the science of translation and its recognized principles.